Gambaran Nutrisi Lansia Di Panti Jompo Dinas Sosial Binjai - Desy Lustiyani Rajagukguk; Juniwati B, Darwita (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Elderly is a condition where every human being who has a long life will definitely pass through the elderly phase which occurs naturally. A person is said to be elderly if he is more than 60 years old and starts after retirement, because as he ages he experiences biological, physical, psychological and social changes. As age increases, all organ functions have reached their maximum peak, so what is happening now is a decline in organ function. Many elderly people in Indonesia experience nutritional deficiencies, with 31% experiencing undernutrition (BMI 16.5-18.49%) and 1.8% overnutrition. Malnutrition is often caused by social and economic problems and also due to disease, if calorie consumption is too low than required then body weight is less than normal. This research is a quantitative descriptive study which aims to determine the total BMI value and type of nutritional intake in the elderly. The research was carried out using measurements and observations carried out at one time only with the inclusion criteria being elderly people who could be communicated with. The research results were obtained from 18 samples experiencing malnutrition and 20 samples at risk of experiencing malnutrition, while for measuring the BMI of the elderly, the results obtained were 0=BMI <19; there were 10 people, value 1=BMI 19-21; there are 29 people, value 1=BMI 21-23: there are 6 people and value 3=BMI > 23; there are 5 people.